Implementasi Persetujuan Bangunan Dan Gedung (PBG) Berbasis Web (SIMBG) Di Kecamatan Ampek Angkek - Mira Susanti; Roni Ekha Putera (Jurnal Mirai Management, 2023)
This research focuses on the implementation of a web-based Building Permit (BP) system in Kecamatan Ampek Angkek, Agam Regency. The study adopts a qualitative research design with a descriptive analysis approach to explore the realities and phenomena associated with the web-based system. The research aims to understand the challenges and obstacles faced during the implementation of the system and proposes effective strategies for improvement. Several key hurdles have been identified, including limited internet access, a shortage of certified building design experts, the need for qualified and skilled staff, compliance issues among users, insufficient funding, and the absence of local regulations for building approvals. To address these challenges, the study suggests the following recommendations. Firstly, thorough preparation and planning are essential in developing the web-based system to meet the specific needs and challenges of the region. Secondly, ensuring the availability of robust ICT infrastructure and secure hardware and software is crucial for efficient system performance. Thirdly, obtaining support and cooperation from all stakeholders, including public awareness campaigns, will promote active participation and engagement in the new system. Investing in human resource development and training is recommended to equip staff with the necessary skills to manage and utilize the web-based system effectively. Moreover, fostering a comprehensive understanding of existing regulations and requirements is vital to facilitate smooth and streamlined building permit processes. Additionally, expediting the issuance of local regulations governing Building Permit approvals is proposed to provide clear guidelines and enhance the system's effectiveness. Finally, if necessary, engaging the services of permit consultants can offer a practical solution to aid applicants in navigating the complex permit procedures. Keywords: Implementation, PBG, SIMBG, Kecamatan Ampek Angkek